Recovery of Microalgae Protein using Membrane Fractionation and Enzymatic Hydrolysis - Henriques, Carolina Fernandes (2023)
Microalgae protein serves as an alternative protein source with nutritional advantages and functional properties. Finding efficient methods to extract and recover proteins from microalgae cells is a critical goal in that context. Throughout this work, the first operations were carried out in a recently commissioned membrane system at the company A4F with the purpose of protein recovery from three microalgae species: Chlorella sorokiniana, Nannochloropsis gaditana, and Arthrospira platensis. After drying of the membrane products, powders from C.sorokiniana and N.gaditana had a composition of 24% and 60% of protein on a dry weight basis, respectively. The powder from A.platensis had 43% undifferentiated protein and 42% phycocyanin, both in DW basis. Enzymatic hydrolysis provides an alternative method for protein recovery. The enzymatic hydrolysis process was carried out with carbohydrases at a temperature of 50ºC for a duration of 5 hours. This process utilized a defatted biomass rich in insoluble proteins and carbohydrates, which represents a by-product of a microalgae biorefinery. The enzyme Celluclast did not significantly increase protein solubilization. Viscozyme led to continuous protein increases with higher enzyme dosages, resulting in a 1.4-fold increase at the dosage of 0.6 mL/g DW and a 2.8-fold increase at the dosage of 1.8 mL/g DW. An In Vitro Protein Digestibility (IVPD) protocol was developed to evaluate the digestibility of the defatted biomass both before and after enzymatic hydrolysis treatment. The results showed that 32% of the defatted biomass was digestible, and the treatment with Celluclast and Viscozyme did not significantly enhance digestibility, except for a notable increase to 75% digestibility achieved with the higher Viscozyme dosage of 1.8 mL/g DW.